Empowering elementary school teachers in garut regency to implement deep learning-based differentiated learning for civic literacy - Faisal Sadam Murron; Shahris Haikal; Sendi Fauzi Giwangsa; Mubarok Somantri; Fatih Nur Farhan; Azmi Nurbarlian Ramadhan; Waysqotnie Pramuditya (Universitas Sebelas Maret, 2025)
The implementation of Merdeka Curriculum in Indonesia demands significant pedagogical transformation, particularly in developing civic literacy through student-centered approaches. This study aims to analyze the effectiveness of teacher empowerment programs in enhancing elementary school teachers' competencies to implement deep learning-based differentiated learning for civic literacy development. This research employed a mixed-methods approach combining quantitative and qualitative data collection within an action research framework following the Kemmis and McTaggart model. The study involved 21 elementary school teachers in Garut Regency selected through purposive sampling. Data were collected using validated questionnaires (Cronbach's Alpha = 0.89) measuring 15 indicators of teacher understanding, complemented by in-depth interviews and classroom observation protocols. Quantitative data were analyzed using descriptive statistics and N-Gain analysis, while qualitative data underwent thematic analysis following Braun and Clarke's framework. Results demonstrated significant improvements in teachers' competencies, with differentiated learning implementation scores increasing from 3.38 to 4.80 (N-Gain = 0.88, high category) and deep learning-based instruction from 3.95 to 4.70 (N-Gain = 0.71, high category). The study concludes that participatory empowerment programs integrating theoretical foundations with practical implementation effectively enhance teachers' pedagogical competencies.